The Girl Who Takes an Eye for an Eye - Lagercrantz, David; Larsson, Stieg 1954-2004.; Goulding, George (Translator) (New York : Alfred A. Knopf, 2017)
"Lisbeth Salander, the girl with the dragon tattoo, the brilliant hacker, the obstinate outsider, the volatile seeker of justice for herself and others--even she has never been able to uncover the most telling facts of her traumatic childhood, the secrets that might finally, fully explain her to herself. Now, when she sees a chance to uncover them once and for all, she enlists the help of Mikael Blomkvist, the editor of the muckraking, investigative journal Millennium. And she will let nothing stop her"--Amazon.com.
Keywords: Blomkvist, Mikael -- (Fictitious character) -- Fiction; Salander, Lisbeth -- (Fictitious character) -- Fiction; Journalists -- Fiction; Hackers -- Fiction; Stockholm (Sweden) -- Fiction; Detective and mystery fiction; Thrillers (Fiction)